2020
DOI: 10.1155/2020/9292163
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Patients with Psoriasis Seen in the Department of Dermatology, Antananarivo, Madagascar

Abstract: Background. Psoriasis is a chronic, inflammatory, and multifactorial dermatosis that impairs quality of life (QoL). Health-related QoL has become an important element in medical decision-making along with the effectiveness and the harmlessness of the treatments. Objective. To assess the impact of psoriasis in the QoL of patients with psoriasis by using the DLQI scales. Methods. A cross-sectional study from January to June 2018 was conducted in the Department of Dermatology of the University Hospital Joseph Ras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
1
7
1
Order By: Relevance
“…According to some previously published reports, mean DLQI scores for patients with psoriasis can be even lower: 9.16 pts according to Lin et al [ 47 ], 8 pts according to Moradi et al [ 48 ], and 6.13 pts according to Rencz et al [ 49 ]. However, some authors reported higher DLQI scores than in the present study: 13.8 pts according to Sendrasoa et al [ 50 ], 13.32 pts according to An et al [ 51 ], and approximately 14 pts according to Kowalewska et al [ 52 ]. Finally, mean DLQI scores in some studies were only slightly lower than in our patients: 12 pts according to Martínez-García et al [ 53 ], 12.4 pts according to Jung et al [ 54 ], and 12.61 according to Kouris et al [ 55 ].…”
Section: Discussioncontrasting
confidence: 72%
“…According to some previously published reports, mean DLQI scores for patients with psoriasis can be even lower: 9.16 pts according to Lin et al [ 47 ], 8 pts according to Moradi et al [ 48 ], and 6.13 pts according to Rencz et al [ 49 ]. However, some authors reported higher DLQI scores than in the present study: 13.8 pts according to Sendrasoa et al [ 50 ], 13.32 pts according to An et al [ 51 ], and approximately 14 pts according to Kowalewska et al [ 52 ]. Finally, mean DLQI scores in some studies were only slightly lower than in our patients: 12 pts according to Martínez-García et al [ 53 ], 12.4 pts according to Jung et al [ 54 ], and 12.61 according to Kouris et al [ 55 ].…”
Section: Discussioncontrasting
confidence: 72%
“…In the study conducted by Sendrasoa et al among psoriatics from Madagascar, 46 mean DLQI was 13.8 pts; deterioration in the quality of life was more evident in young patients, single persons, and those with medium level education. Importantly, an increase in PASI scores was associated with a significant deterioration of the quality of life in the study patients (p = 0.002).…”
Section: Discussionmentioning
confidence: 87%
“…This DLQI score was higher than the results reported in a QoL assessment study with a mean DLQI score of 6.3 in patients with alopecia by Zhang and Zhang (2017) . Meanwhile, Sendrasoa et al (2020) reported a very poor QoL in patients with psoriasis (mean DLQI: 13.8). Another study ( Davidson et al, 2010 ) in which the SF-36 questionnaire was used to assess QoL reported worse outcomes in upper limb amputees than in lower limb amputees.…”
Section: Discussionmentioning
confidence: 99%